Effects of moxifloxacin on the proarrhythmic surrogate markers in healthy Filipino subjects: Exposure-response modeling using ECG data of thorough QT/QTc study - Suchitra Matsukura; Yuji Nakamura; Kiyotaka Hoshiai; Takashi Hayashi; Tadashi Koga; Ai Goto; Koki Chiba; Nur Jaharat Lubna; Mihoko Hagiwara-Nagasawa; Hiroko Izumi-Nakaseko; Kentaro Ando; Atsuhiko T. Naito; et al. (Elsevier, 2018)
Effects of moxifloxacin on QTc as well as proarrhythmic surrogate markers including J-Tpeakc, Tpeak-Tend and short-term variability (STV) of repolarization were examined by using both standard E14 time-based evaluation and exposure-response modeling. The study was conducted with a single-blind, randomized, single-dose, placebo-controlled and two-period cross-over design in healthy Filipino subjects. QT interval was corrected by Fridericia's formula (QTcF). In the E14 time-based evaluation of ECG data, the largest ΔΔQTcF with 90% confidence interval was 14.1 ms (11.2-16.9) with Cmax of 3.39 μg/mL at 3 h post-dose (n = 69; male: 35, female: 34), indicating a positive effect on the QTcF. Moxifloxacin significantly increased the ΔΔJ-Tpeakc and ΔΔTpeak-Tend, whereas the ΔΔSTV was not altered. Meanwhile in the exposure-response modeling of the same ECG data, the slope of moxifloxacin plasma concentration-ΔΔQTcF relationship was 4.84 ms per μg/mL and the predicted ΔΔQTcF with 90% confidence interval was 13.8 ms (13.1-15.1) at Cmax, also indicating a positive effect on the QTcF. Importantly, results in each proarrhythmic surrogate marker obtained by the exposure-response modeling also showed high similarity to those obtained by the E14 statistical evaluation. Thus, these results of moxifloxacin may become a guide to estimate proarrhythmic potential of new chemical entities. Keywords: ICH E14, Moxifloxacin, Thorough QT study, Exposure-response modeling, J-Tpeak